Is Concha Bullosa Associated with Nasal Septum Deviation and Mucosal Thickening of the Maxillary Sinuses? A Cone Beam Computed Tomography Study - Ruiz, Débora Costa; Souza, Letícia de Andrade; Farias-Gomes, Amanda; Freitas, Deborah Queiroz (International Archives of Otorhinolaryngology, 2025)
Concha bullosa (CB) is an anatomical variation that can affect respiratory function. Therefore, identifying it is important.To evaluate the prevalence of CB and its association with the side of pneumatization (right/left), nasal septum deviation (NSD), and mucosal thickening of the maxillary sinuses using cone-beam computed tomography (CBCT) exams from a Brazilian subpopulation. Also, to investigate the association between CB, sex and age.There were 297 CBCT exams assessed by two examiners who evaluated the presence of CB (> 50% pneumatization of the turbinate's height), NSD (deviation point of the nasal septum and crista galli angle >9o), and mucosal thickening of maxillary sinuses (mucosa around the sinus walls > 3 mm in height). The association between CB and side, NSD, mucosal thickening of the maxillary sinuses, sex, and age were evaluated by the chi-squared and Fisher's exact tests (α = 5%).A total of 208 CB was found, corresponding to 11.7% of the evaluated turbinates, being more prevalent in the middle one (p < 0.0001). Considering all exams, 132 (44.4%) had at least one CB. There was an association between the presence of middle left CB with NSD (p = 0.028). No other significant associations were found (p > 0.05).Almost half of the CBCT exams had at least one CB. Its prevalence was higher in the middle turbinate. There seems to be an association between middle CB and NSD. As for the other variables, no strong association was found.
Keywords: concha bullosa; nasal septum deviation; maxillary sinus; diagnostic imaging; cone-beam computed tomography